1993
DOI: 10.1002/pssa.2211370224
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Passivation of the Dislocation-Related D-Band Luminescence in Silicon

Abstract: The influence of atomic hydrogen on the D‐band photoluminescence in silicon is investigated. In contrast to other studies, a preferential passivation of the D1‐ and D4‐band intensities but an increase in the intensities of the D2 and D3 bands after hydrogen passivation at 300 °C are observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…1) are in good agreement with previous results [5,13], and demonstrate that the deformations at 700 C were performed under clean conditions. Actually, the three parameters tuned in the experiments (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…1) are in good agreement with previous results [5,13], and demonstrate that the deformations at 700 C were performed under clean conditions. Actually, the three parameters tuned in the experiments (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, the effect of transition metal [3,4] or hydrogen impurities [5,6] has been extensively studied. However, the effect of oxygen has been the object of less attention although it is one of the most important impurities in Si.…”
Section: Introductionmentioning
confidence: 99%
“…In previous reports, Dube and Hanoka [81] reported that hydrogen was able to passivate dislocations for depths up to 250 µm in string ribbon silicon. Furthermore, Weronek et al [86] reported the hydrogenation of the extended defects-related D-Band luminescence in silicon. In detail, it was found that hydrogenation at 300 • C are able to reduce the D1 and D4 band intensities but increase the intensities of the D2 and D3 bands.…”
Section: Passivation Of Extended Defectsmentioning
confidence: 99%
“…There has been an extensive study of dislocation-related photoluminescence in Si [5][6][7] and Si 1−x Ge x alloys [8][9][10]. From an experimental point of view, D1/D2 and D3/D4 bands have similar origins due to similarities in their optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…From an experimental point of view, D1/D2 and D3/D4 bands have similar origins due to similarities in their optical properties. The radiative recombination process in these alloys can originate either from impurity-related transitions or from the intrinsic property of the dislocation [6].…”
Section: Introductionmentioning
confidence: 99%